Analysis of S2 (Spherical) Geometry Library Algorithm for GIS Geocoding Engineering - Risma Ekawati; Untung Suprihadi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
Geocoding is a common technique to transform address information into digital latitude/longitude format. One of the engineering conversions can be used is Google Maps based on S2 (Spherical) Geometry Library algorithm. This journal explains the quality analysis of the algorithm using geocoding quality matrix testing from hundreds of address data samples particularly on three cities in Indonesia-Jakarta, Bandung, and Balikpapan. However, the result of this research concludes that completeness of address information will affect its overall fourth matrix quality and the linkages of it such as transform success rate, landmark exactness, the score of accuracy and range of radius in meter.